Anastomosing hemangioma with extensive fatty stroma in the retroperitoneum - Ananthvikas Jayaram; Marie Therese Manipadam; Paul Mazhuvanchary Jacob (Wolters Kluwer Medknow Publications, 2018)
Anastomosing hemangiomas are a recently recognized benign vascular neoplasm, first described by Montgomery and Epstein in 2009. A few cases have been described in the genitourinary tract, especially in the renal hilum. These are fairly well-demarcated lesions with lobules of sinusoidal-like capillaries lined by hobnail endothelial cells containing eosinophilic hyaline globules in the cytoplasm. Extramedullary hematopoiesis has been described in a few cases, along with large feeding vessels. A predominant adipocytic component has been described in only one case.[9] We describe a case of a retroperitoneal anastomosing hemangioma occurring in an extrarenal site in a 53-year-old female, followed by a review of the current literature.